Digital branding assistance for MSMEs as a marketing strategy in the Industry 4.0 Era - Novia, Cahyuni; Tania, Anggun Putri; Nafilah, Naila; Afril, Hadilah; Cahyati, Redita Sulis; Nur, Syakila Sukma (Jurnal Pengabdian Masyarakat, 2025)
Purpose: This program aimed to assist MSMEs “Solali” restaurant in developing creative and innovative branding strategies through digital technology to strengthen competitiveness in the Industry 4.0 era. Method: Activities were conducted through participatory mentoring, including needs assessment, training on digital branding concepts, and hands-on workshops for creating and applying digital marketing content, especially via social media. Practical Applications: The program provided “Solali” restaurant with actionable digital branding strategies to improve brand awareness, engage customers, and expand market reach, enabling a transition from traditional to modern marketing. Conclusion: The mentoring enhanced participants’ skills and understanding of digital branding, resulting in increased online visibility and a stronger brand image. These outcomes are expected to support sales growth and business sustainability.